Cross-Sectional Estimation of U.S. Demand for Beef Products: A Censored System Approach - Steven T. Yen (Journal of Agricultural and Resource Economics, 2002)
Demands for beef products are investigated using the U.S. Department of Agriculture's 1987-88 Nationwide Food Consumption Survey data. The censored translog demand system is estimated with full-information and simulated maximum-likelihood procedures. These procedures represent different approaches to evaluation of multiple probability integrals in the likelihood function, but produce very similar parameter and elasticity estimates. Findings suggest sociodemographic variables play important roles in the demand for beef, and that demand for different cuts of beef should be treated differently.